2016
DOI: 10.1093/ecco-jcc/jjw032
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Granulocyte/Monocyte Apheresis in Steroid-Dependent Active Ulcerative Colitis with Insufficient Response or Intolerance to Immunosuppressants and/or Biologics [the ART Trial]: 12-week Interim Results

Abstract: Background and Aims:Patients with active, steroid-dependent ulcerative colitis with insufficient response or intolerance to immunosuppressants and/or biologic therapies have limited treatment options. Adacolumn, a granulocyte/monocyte adsorptive apheresis device, has shown clinical benefit in these patients. This study aimed to provide additional clinical data regarding the safety and efficacy of Adacolumn in this patient subgroup.Methods:This single-arm, open-label, multicentre trial [ART] was conducted at 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 29 publications
3
39
1
Order By: Relevance
“…Clinical remission was achieved in 30.0% of patients with previous immunosuppressant and biologic failure. These results are consistent with previous studies in Japan [25].…”
Section: -1 Medical Treatmentsupporting
confidence: 94%
“…Clinical remission was achieved in 30.0% of patients with previous immunosuppressant and biologic failure. These results are consistent with previous studies in Japan [25].…”
Section: -1 Medical Treatmentsupporting
confidence: 94%
“…Nevertheless, a large scale randomized controlled trial (RCT) conducted in North America failed to show efficacy in the induction of clinical remission or response in patients with moderate to severe UC 20 . The difference in GMA efficacy between this RCT and other studies 8 16 may be attributed to demographic/disease characteristics, medical histories, and past exposure to pharmacologic preparations. A subset of patients who might or might not respond to GMA has not been fully identified.…”
Section: Introductionmentioning
confidence: 67%
“…In Japan since April 2000 when GMA was approved as one treatment option for patients with active UC by the Japan Ministry of Health, it has been widely used for patients with UC, and to our knowledge, it is now available in the European Union countries. Multiple studies in Japan 8 12 and Europe 13 16 found that GMA was safe and therapeutically effective in patients with active UC. Additional evidence to support a therapeutic benefit from GMA should lead to a reduced need for pharmacologic preparations like corticosteroids, immunosuppressants, and biologicals which are associated with serious adverse side effects as additional morbidities 17 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto, a large number of articles mostly from Japan, [51][52][53][54][55][56][57][58][59][60][61][62][63] Europe, [64][65][66][67][68][69][70][71][72][73][74][75][76][77] and the USA 78,79 have described the efficacy of GMA in patients with IBD. The clinical application of GMA with the Adacolumn began following a pioneering multicentre clinical trial by Shimoyama, et al 80 Since then, GMA has been widely applied in Japan and in the European Union (EU) countries to treat patients with IBD.…”
Section: Clinical Efficacy Of Gma In Patients With Ucmentioning
confidence: 99%
“…Further, the mean time to remission was 28.1 days, in group 1 and 16.3 days in group 2. In spite of these outcomes, our views are that the efficacy of GMA is time dependent, may take several weeks to be seen . As reviewed above, in patients with active IBD, large numbers of myeloid lineage leucocytes are found within the mucosal tissue, which may take several weeks to clear in spite of CAI showing clinical remission .…”
Section: Introductionmentioning
confidence: 99%